Distinction between "Prevention" and "Protection" in International Law on the Sea - Valiullina, Ksenia; Khodzhiyev, Alisher; Sagitov, Sergey (Journal of History Culture and Art Research, 2018)
In the light of the increasingly intensive use of the spaces and resources of the World Ocean, the problem of its rapid pollution is one of the new challenges and threats to the security of people. Protection of the World Ocean from pollution is a key measure in the system to ensure universal environmental security, since it is to the Ocean that rightfully has an exceptional role in ensuring life on our planet. The World Ocean is an integral system directly influencing the climate of the whole planet, the plant and animal world, the processes of life and human activity. At the same time, this part of the Earth’s hydrosphere is the most polluted from all natural objects. Protecting and securing the World Ocean from pollution is possible only on the basis of scientific research conducted jointly by representatives of various branches of science: geography and physics, chemistry and ecology, oceanography and geology, and many others. However, it is possible to identify the actions of states necessary to ensure the protection and securing the oceans and, above all, to provide for international standards binding for all states in this field only within the framework of international law. It is important to highlight the fact that international law, in the context of the above-mentioned relations, fulfills two most important functions: regulative and protective, where the latter both in science and in legislation is determined through such related categories as "protection", "securing" and "preservation". Nevertheless, today, we have to state the fact that there is no single point of view on the delineation of these close but not identical concepts.